Possibility to Identify Projectiles and Other Components of the Cartridges by Consideration on Barrels and Projectiles Types - Dzindzibadze, Giorgi (European Scientific Journal, ESJ, 2022)
There are basically three types of barrels - polygonal rifling, traditional (conventional) rifling, and smooth bore, accordingly, the internal shape of the barrels is different. Therefore, the projectiles passed in these barrels have different marks of form, some more depicted, some less so. Identifying private signs is necessary for comparison. If such marks do not remain on the surface of the bullet, then it will be unusable for identification, because, the identification process should be based on a comparison of general and individual marks. This issue has been explored and reflected in the article, in which case it is possible to conduct identification research on bullets. The article also analyzes what issues the expert should consider when identifying. It is probably clear to everyone that it is impossible to conduct research of this scale on objects (shots, pellets, plastic containers) that do not have sufficient identification marks. Reasoned conclusion, which should be used in court as evidence, should be based on a combination of durable individual barrel channel marks with other bullets, or with a combination of durable individual barrel marks of the experimental weapon.